Framework Fabrication with Rib Cartilage in Partial and Total Nasal Reconstruction - von Gregory, Henning Freiherr; Fischer, Helmut; Eppstein, Ron Julius; Gubisch, Wolfgang (Facial Plastic Surgery, 2014)
The framework reconstruction of the nose is a significant and complex component of its partial or total reconstruction. On the one hand, the design of the individual framework parts is based on the anatomic nature of available rib or ear cartilage, which must on the other hand be adapted to the anatomic characteristics of the defect. The framework parts must be anchored not only to each other but also stably to the facial skeleton. The symmetry of the framework reconstruction is an essential component of the aesthetics of the reconstructed nose. If these points are already considered in planning, the reconstruction of the nasal framework can be standardized insofar as the same principles for the basic design of the individual parts as well as stable solutions for the anchoring points can be chosen. With reproducible techniques, functionally and aesthetically good to very good results can be achieved, including in the long term. The surgeon must possess special skills in the field of nasal reconstruction to correctly choose, apply, and combine the various techniques of nasal framework reconstruction.
Keywords: nasal framework; nasal reconstruction; paramedian forehead flap; rib cartilage; diced cartilage